Optimal sequencing of enzalutamide and abiraterone acetate plus prednisone in metastatic castration-resistant prostate cancer: a multicentre, randomised, open-label, phase 2, crossover trial. Issue 12 (December 2019) - Khalaf, Daniel J; Annala, Matti; Taavitsainen, Sinja; Finch, Daygen L; Oja, Conrad; Vergidis, Joanna; Zulfiqar, Muhammad; Sunderland, Katherine; Azad, Arun A; Kollmannsberger, Christian K; Eigl, Bernhard J; Noonan, Krista; et al.
Summary: Background: Abiraterone acetate plus prednisone and enzalutamide are both used for the treatment of metastatic castration-resistant prostate cancer. We aimed to determine the best sequence in which to use both drugs, as well as their second-line efficacy. Methods: In this multicentre, randomised, open-label, phase 2, crossover trial done in six cancer centres in British Columbia, Canada, we recruited patients aged 18 years or older with newly-diagnosed metastatic castration-resistant prostate cancer without neuroendocrine differentiation and Eastern Cooperative Oncology Group performance status 2 or less. Patients were randomly assigned (1:1) using a computer-generated random number table to receive either abiraterone acetate 1000 mg orally once daily plus prednisone 5 mg orally twice daily until PSA progression followed by crossover to enzalutamide 160 mg orally once daily (group A), or the opposite sequence (group B). Treatment was not masked to investigators or participants. Primary endpoints were time to second PSA progression and PSA response (≥30% decline from baseline) on second-line therapy, analysed by intention-to-treat in all randomly assigned patients and in patients who crossed over, respectively. The trial is registered with ClinicalTrials.gov, NCT02125357 . Findings: Between Oct 21, 2014, and Dec 13, 2016, 202 patients were enrolled and randomly assigned to either group A (n=101) or group B (n=101). At the time of data cutoff, 73 (72%) patients in group A and 75 (74%) patients in group B had crossed over. Time to second PSA progression was longer in group A than in group B (median 19·3 months [95% CI 16·0–30·5] vs 15·2 months [95% CI 11·9–19·8] months; hazard ratio 0·66, 95% CI 0·45–0·97, p=0·036), at a median follow-up of 22·8 months (IQR 10·3–33·4). PSA responses to second-line therapy were seen in 26 (36%) of 73 patients for enzalutamide and three (4%) of 75 for abiraterone (χ 2 p<0·0001). The most common grade 3–4 adverse events throughout the trial were hypertension (27 [27%] of 101 patients in group A vs 18 [18%] of 101 patients in group B) and fatigue (six [10%] vs four [4%]). Serious adverse events were reported in 15 (15%) of 101 patients in group A and 20 (20%) of 101 patients in group B. There were no treatment-related deaths. Interpretation: Enzalutamide showed activity as a second-line novel androgen receptor pathway inhibitor, whereas abiraterone acetate did not, leading to a longer time to second PSA progression for the sequence of abiraterone followed by enzalutamide than with the opposite treatment sequence. Our data suggest that using a sequencing strategy of abiraterone acetate followed by enzalutamide provides the greatest clinical benefit. Funding: Canadian Cancer Society Research Institute, Prostate Cancer Canada, Movember Foundation, Prostate Cancer Foundation, Terry Fox New Frontiers Program, BC Cancer Foundation, Jane and Aatos Erkko Foundation, Janssen, and Astellas.